2021
DOI: 10.1016/j.jvs.2021.04.018
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary analysis of late structural failures of the Navion stent graft in the treatment of descending thoracic aortic aneurysms

Abstract: Objective: Patients in the Valiant Evo U.S. and international clinical trials had positive short-term outcomes; however, late structural failures, including type IIIb endoleaks have been recently discovered. Type IIIb endoleaks are serious adverse events because the repressurization of the aneurysm sac increases the risk of rupture. The purpose of the present study was to detail the imaging patterns associated with the structural failures with the aim of increasing awareness of failing graft presentation, earl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…14,15 While there are benefits to reducing the profile, it may lead to a loss of overall performance and durability of the device. [4][5][6][7][8] Zenith Alpha AAA is a new-generation low-profile endovascular graft that is already available in Europe, Australia, Canada, and Brazil; however, reports on the clinical results are currently lacking in the literature with only 1 study reporting 30 days clinical result. 11 In this report, we retrospectively evaluated consecutive 79 patients in the initial launch of Zenith Alpha AAA in Japan, and found that sac shrinkage of >5 mm was achieved in 42.2% of patients, with satisfactory freedom from late complication rate of 90.8% at 12 months.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…14,15 While there are benefits to reducing the profile, it may lead to a loss of overall performance and durability of the device. [4][5][6][7][8] Zenith Alpha AAA is a new-generation low-profile endovascular graft that is already available in Europe, Australia, Canada, and Brazil; however, reports on the clinical results are currently lacking in the literature with only 1 study reporting 30 days clinical result. 11 In this report, we retrospectively evaluated consecutive 79 patients in the initial launch of Zenith Alpha AAA in Japan, and found that sac shrinkage of >5 mm was achieved in 42.2% of patients, with satisfactory freedom from late complication rate of 90.8% at 12 months.…”
Section: Discussionmentioning
confidence: 99%
“…Durable repair has become a considerable topic in the EVAR procedure and is also the biggest concern with lowprofile endovascular graft. [4][5][6][7][8] The conventional Zenith endovascular graft, which is one of the longest selling EVAR devices on the market, has been reported to have good long-term results. 9,10 One of the strengths of conventional Zenith endovascular grafts is the greater early sac shrinkage observed compared with other devices.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients treated with the Val- A total of 50 patients who suffered a blunt aortic trauma were enrolled in a study to assess the Zenith Alpha thoracic endovascular graft (Cook Medical, Bloomington, IN, US, Figure 4). During a mean 21-month follow-up, a 30% incidence of in-graft thrombus resulted in the manufacturer's voluntary removal of the blunt-aortic-trauma indication for this device [23].…”
Section: Current Tevar Platformsmentioning
confidence: 99%